2009
DOI: 10.1016/s1472-6483(10)60053-3
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell models of Huntington disease

Abstract: Huntington disease (HD) is an incurable late-onset neurodegenerative disorder caused by a CAG repeat expansion in exon 1 of the HD gene (HTT). The major hallmark of disease pathology is neurodegeneration in the brain. Currently, there are no useful in-vitro human models of HD. Recently, two human embryonic stem cell (hESC) lines carrying partial (CAG(37)) and fully (CAG(51)) penetrant mutant alleles have been derived from affected IVF embryos identified following preimplantation genetic diagnosis (PGD). Fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 40 publications
1
51
1
1
Order By: Relevance
“…These hESCs with genetic disease inheritance that have unlimited proliferating and self-renewing potential are unique sources to reproduce heredity of diseases in vitro [56,57]. However, only a few studies reported isolation of these cells so far [57][58][59][60][61].…”
Section: Isolation Of Pluripotent Hescs From Hd Embryosmentioning
confidence: 99%
See 4 more Smart Citations
“…These hESCs with genetic disease inheritance that have unlimited proliferating and self-renewing potential are unique sources to reproduce heredity of diseases in vitro [56,57]. However, only a few studies reported isolation of these cells so far [57][58][59][60][61].…”
Section: Isolation Of Pluripotent Hescs From Hd Embryosmentioning
confidence: 99%
“…The HD-hESCs isolated so far ( Table 1) can be considered primed hESCs according to the existing classification [43,62]. They express core pluripotency markers and present a normal karyotype [58][59][60][61]. Only one study demonstrated that HD-hESCs are able to form teratomas [59].…”
Section: Isolation Of Pluripotent Hescs From Hd Embryosmentioning
confidence: 99%
See 3 more Smart Citations